Hospitality education and finance courses: An 'inconvenient' relationship?. (June 2019) - Zopiatis, Anastasios; Lambertides, Neophytos; Savva, Christos S.; Theocharous, Antonis L.
Abstract: Many scholars have investigated the relationship between hospitality education and the discipline of finance. While the world of academia seems to consistently support the importance of finance-related competencies, the literature nevertheless remains inconclusive. This practice paper aims to enhance our conceptual capital on this topic by providing an overview of the aforementioned relationship, and examining the potential role and value of finance-related courses within hospitality education. Moreover, by stressing that a meaningful connection between the two disciplines must be initiated at the academic level, we provide practical recommendations that should be of interest to industry stakeholders.